Ressonância magnética de tórax em portadores de dispositivos cardíacos eletrônicos implantáveis condicionais para RM : contraindicação clássica ou exame seguro? - Rosatti, Silvio Fernando Castro (2015)
The use of Magnetic Resonance Imaging (MRI) as a diagnostic imaging has grown every year due to its great benefits. MRI is a noninvasive test and decisiveness for diagnosis of various diseases and is widely used around the world. With the extension of human longevity, it is increasingly necessary to use new technologies for diagnosis and treatment of diseases. It is known that with increasing age, the individual develops certain diseases that require surgical correction resulting often the implant fixtures as, Cardiac Implantable Electronic Devices (DCEIs). Even though technologies that broke paradigms and transformed lives, extending life expectancy and facilitating diagnoses that were previously impossible and bad, these two medical advances were antagonists until recently, strictly forbidden and that patients with DCEI do use the examination RM due to the interference that this test could cause the DCEI and so harm the health of the patient. As this diagnostic imaging technology cannot be applied to most existing implants, it may be necessary to use alternatives with side effects or less valuable diagnostic information. Because it is an important and necessary for the progress of medical diagnostic advance, the potential risks and the influence of MRI on pacemakers have become research topic over the last ten years. As a result, we acquired a comprehensive understanding of the associated problems. This understanding and solutions to these problems have been integrated in the development of secure devices for MRI (MRI Pro). The objectives of this study were to determine if there is interference DCEI the image generated by Thoracic MRI and thus to understand their influence on the outcome of the review, and determine whether there were significant changes in the operation of this DCEI. Thoracic MRI was performed in 20 patients with DCEIs. The generated image, artifacts and pre and post test parameters were analyzed and compared; coming to the conclusion that Thoracic MRI in patients with DCEIs Pro MRI can be performed safely without changing the operation of the devices and without damaging the image of RM, since some rules and conditions are followed.